Arterial Stiffness Is Associated With QTc Interval Prolongation in Patients With Heart Failure. Issue 3 (May 2018) - Al-Zaiti, Salah; Saba, Samir; Pike, Rodolfo; Williams, Jennifer; Khraim, Fadi
Background: A prolonged corrected QT (QTc) interval is a known risk factor for adverse cardiac events. Understanding the determinants and physiologic correlates of QTc is necessary for selecting proper strategies to reduce the risk of adverse events in high-risk patients. We sought to evaluate the role of arterial stiffness in heart failure as a determinant of QTc prolongation. Method: This was an observational study that recruited ambulatory heart failure patients (New York Heart Association Classes I–II) from an outpatient heart failure clinic. In the supine resting position, consented patients underwent noninvasive 12-lead electrocardiograph (ECG) and hemodynamic monitoring using BioZ Dx impedance cardiography. ECGs were evaluated by a reviewer blinded to clinical data, and QTc interval was automatically computed. Patients with pacing or bundle branch block (BBB) were analyzed separately. Strengths of associations were evaluated using Pearson's r coefficients and multivariate linear regression. Results: The final sample ( N = 44) was 62 ± 13 years of age and 64% male with ejection fraction of 34% ± 12%. At univariate level, QTc interval moderately ( r > .50) correlated with cardiac output, left cardiac work index, systemic vascular resistance, and total arterial compliance in patients with intrinsically narrow QRS complexes. At the multivariate level, increasing systemic vascular resistance and decreasing total arterial compliance remained independent predictors of widening QTc interval in this group ( R 2 = .54). No significant correlations were seen in patients with pacing or BBB. Conclusions: In the absence of conduction abnormalities, magnitude of arterial stiffness, an indirect measure of endothelial dysfunction, is associated with QTc interval prolongation.